Method for cutting composite material

By forming processing grooves in the optical functional layer and protective layer, and using ultrashort pulse lasers to form processing marks in the brittle material layer, combined with mechanical fracture or thermal heating, the problem of easy cracking at the end face of the brittle material layer in the prior art is solved, and efficient severing of composite materials and process simplification are achieved.

CN115485097BActive Publication Date: 2026-11-06NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080099699.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-11
Filing Date
2020-12-02
Publication Date
2026-11-06
Estimated Expiration
2040-12-02

AI Technical Summary

Technical Problem

Existing technologies cannot effectively cut off composite materials with a resin optical functional layer on one side and a resin protective layer on the other side in one go without causing cracks on the end face of the brittle material layer.

Method used

A CO2 laser source is used to form a processing groove in the optical functional layer and the protective layer, and an ultrashort pulse laser is used to form a processing mark in the brittle material layer, ensuring that the width of the processing groove is greater than the diameter of the ultrashort pulse laser spot. The truncation is achieved by combining mechanical fracture or thermal heating methods.

Benefits of technology

It enables efficient severing of composite materials without causing cracks at the end faces of brittle material layers, simplifying the manufacturing process and reducing labor and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115485097B_ABST
    Figure CN115485097B_ABST
Patent Text Reader

Abstract

This invention provides a method for cutting composite materials without causing cracks at the end face of brittle material layers. The method of cutting the composite material (10) on each side of the brittle material layer (1) of the present invention includes: a processing groove forming step in which the optical functional layer is irradiated with a laser (L1) oscillating from a first laser source (20) along a predetermined cutting line (DL) of the composite material to form a first processing groove (21), and the protective layer is irradiated with a laser (L2) oscillating from a second laser source (30) along the predetermined cutting line (DL) to form a second processing groove (31); and a brittle material removal step in which the brittle material layer is irradiated with a laser (L3) oscillating from an ultrashort pulse laser source (40) along the predetermined cutting line to form a processing mark (11), wherein the resin forming the protective layer is removed in such a way that the width (W) of the second processing groove is greater than or equal to the spot diameter (D) at the irradiation position of the brittle material layer by the laser oscillating from the ultrashort pulse laser source in the processing mark forming step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for cutting a composite material having a resin-based optical functional layer (e.g., a polarizing film) laminated on one side of a brittle material layer and a resin-based protective layer (e.g., a protective film) laminated on the other side of the brittle material layer. In particular, this invention relates to a method for cutting the composite material without causing cracks at the end faces of the brittle material layer. Background Technology

[0002] In recent years, in addition to the development of thinner and more precise LCD panels, LCD panels with touch sensor functionality have been used in a wide range of fields, from mobile phones to information displays, in order to make the interface more diverse.

[0003] Recently, from the perspective of thinness and lightness, liquid crystal panels with embedded liquid crystal cells that have touch sensors set in the glass substrate of the liquid crystal cell have been introduced.

[0004] On the other hand, film-like glass, also known as thin glass, is increasingly attracting attention as the front panel disposed on the outermost surface of a liquid crystal panel. Since thin glass can be rolled into a roll, it has the advantage of being able to adapt to the so-called roll-to-roll manufacturing process, and glass polarizing films integrated with polarizing films have been proposed (for example, see Patent Document 1).

[0005] A glass polarizing film can be bonded to an embedded liquid crystal cell to obtain a liquid crystal panel with touch sensor functionality. Therefore, compared with conventional liquid crystal panels that use tempered glass as the front panel, the manufacturing process can be greatly simplified.

[0006] As a method for cutting a composite material, such as a glass polarizing film, into a desired shape / size corresponding to its application by stacking a brittle material layer made of glass or the like and an optical functional layer made of a polarizing film, the method described in Patent Document 2 has been proposed.

[0007] The method described in Patent Document 2 is as follows: the optical functional layer (resin layer in Patent Document 2) of the composite material is irradiated with a laser oscillating from a laser source such as a CO2 laser source along the predetermined cut-off line of the composite material to remove the resin forming the optical functional layer; then the brittle material layer is irradiated with a laser oscillating from an ultrashort pulse laser source (ultrashort pulse laser) along the predetermined cut-off line of the composite material to remove the brittle material forming the brittle material layer, thereby cutting off the composite material.

[0008] The method described in Patent Document 2 has the advantage of not causing cracks on the end face of the brittle material layer after severance.

[0009] Here, for composite materials such as the glass polarizing film described above, which are made by stacking a brittle material layer formed of glass or the like and an optical functional layer formed of a polarizing film or the like, a protective layer, such as a protective film, is generally stacked on the side of the cut composite material sheet opposite to the side of the brittle material layer on which the optical functional layer is stacked, and the product is shipped out. However, since performing the process of stacking a protective layer on each cut composite material sheet requires labor and time, in order to eliminate this labor and time and reduce work hours, it is desirable to have a method that cuts the composite material with the optical functional layer stacked on one side of the brittle material layer and the protective layer stacked on the other side of the brittle material layer in one operation.

[0010] However, Patent Document 2 does not propose a method for cutting off a composite material in one step where an optical functional layer is stacked on one side of the brittle material layer and a protective layer is stacked on the other side of the brittle material layer.

[0011] It should be noted that in Non-Patent Document 1, the processing technology using ultrashort pulse lasers describes the application of the filamentation phenomenon of ultrashort pulse lasers and the application of multifocal optical systems or Bessel beam optical systems to ultrashort pulse laser sources.

[0012] Existing technical documents

[0013] Patent documents

[0014] Patent Document 1: International Publication No. 2013 / 175767

[0015] Patent Document 2: Japanese Patent Application Publication No. 2019-122966

[0016] Non-patent literature

[0017] Non-Patent Document 1: John Lopez et al., "Glass Cutting Using Ultrashort Pulsed Bessel Beams", [online], October 2015, International Congress on Applications of Lasers & Electro-Optics (ICALEO), [accessed July 8, 2015], Internet (URL: https: / / www.researchgate.net / publication / 284617626_GLASS_CUTTING_USING_ULTRASHORT_PULSED_BESSEL_BEAMS) Summary of the Invention

[0018] The problem that the invention aims to solve

[0019] The present invention was made to solve the problems of the prior art as described above. The objective is to provide a method for cutting composite materials that can cut a composite material having a resin-based optical functional layer laminated on one side of a brittle material layer and a resin-based protective layer laminated on the other side of the brittle material layer, and the method does not cause cracks to form on the end face of the brittle material layer.

[0020] Problem Solving Methods

[0021] In order to solve the above problems, the inventors have studied the case of using the method described in Patent Document 2.

[0022] Specifically, for a composite material in which a resin-based optical functional layer is laminated on one side of a brittle material layer and a resin-based protective layer is laminated on the other side of the brittle material layer, it is considered to form a processing groove (first processing groove) in the optical functional layer along a predetermined cut-off line of the composite material using a laser oscillating from a CO2 laser source or the like, and to form a processing groove (second processing groove) in the protective layer along the predetermined cut-off line of the composite material using a laser oscillating from a CO2 laser source or the like. Furthermore, in order to prevent severe thermal degradation of the end face of the cut-off optical functional layer (to minimize the discoloration area associated with thermal degradation), it is considered whether to irradiate the brittle material layer along the predetermined cut-off line of the composite material through the second processing groove with a laser oscillating from an ultrashort pulse laser source (ultrashort pulse laser).

[0023] However, through actual experiments conducted by the inventors, it was found that if the laser output for forming the second processing groove is low and the depth of the second processing groove is too shallow, a through-grain processing mark cannot be formed in the brittle material layer when irradiated with an ultrashort pulse laser, thus preventing the composite material from being cut. On the other hand, it was found that if the laser output for forming the second processing groove is too high, the brittle material layer will suffer thermal damage, and cracks will form on the end face of the brittle material layer starting from the location of the thermal damage when irradiated with an ultrashort pulse laser. Furthermore, it was found that setting the laser output for forming the second processing groove to an appropriate value in order to form a processing mark in the brittle material layer without causing cracks on the end face of the brittle material layer requires very subtle adjustments, making automation difficult.

[0024] To this end, the inventors conducted further research and found that if the second processing groove is formed in such a way that the width of the second processing groove is greater than or equal to the diameter of the spot at the irradiation position of the ultrashort pulse laser on the brittle material layer, then there is no need to make subtle adjustments to the laser output used to form the second processing groove. That is, the composite material can be cut off without causing cracks to form on the end face of the brittle material layer, thus completing the present invention.

[0025] This invention was made based on the insights of the inventors mentioned above.

[0026] In order to solve the above problems, the present invention provides a method for cutting a composite material. This method involves cutting a composite material having a resin-based optical functional layer laminated on one side of a brittle material layer and a resin-based protective layer laminated on the other side of the brittle material layer. The method includes a groove forming step and a machining mark forming step following the groove forming step. In the groove forming step, the optical functional layer is irradiated along a predetermined cutting line of the composite material with a laser beam oscillating from a first laser source to remove the resin forming the optical functional layer, thereby forming a first groove along the predetermined cutting line. Furthermore, the protective layer is irradiated along the predetermined cutting line with a laser beam oscillating from a second laser source. The resin forming the protective layer is removed by the laser emitted from the second processing groove, thereby forming a second processing groove along the predetermined cut-off line; in the processing groove forming step, the brittle material layer is irradiated by a laser emitted from an ultrashort pulse laser source from the second processing groove side along the predetermined cut-off line to remove the brittle material forming the brittle material layer, thereby forming a processing mark along the predetermined cut-off line. In the processing groove forming step, the resin forming the protective layer is removed such that the width of the second processing groove is greater than or equal to the spot diameter at the irradiation position, which is the irradiation position of the brittle material layer by the laser emitted from the ultrashort pulse laser source in the processing mark forming step.

[0027] According to the method of the present invention, in the groove forming step, a first groove and a second groove are formed along a predetermined cut-off line by removing the resin forming the optical functional layer and the resin forming the protective layer. However, in the mark forming step, a mark is formed along the same predetermined cut-off line by removing the brittle material forming the brittle material layer from the second groove side. The second groove formed in the groove forming step is formed with a width greater than or equal to the spot diameter at the irradiation position of the brittle material layer by the laser (ultra-short pulse laser) oscillating from the ultra-short pulse laser source in the mark forming step. Therefore, as discovered by the inventors above, the brittle material layer can be cut off without causing cracks to form on its end face.

[0028] By making the width of the second processing groove greater than the spot diameter at the irradiation position of the ultrashort pulse laser on the brittle material layer, as in the method of the present invention, the energy of the ultrashort pulse laser is less likely to be consumed in the removal of the resin forming the protective layer, but can be fully used for the removal of the brittle material forming the brittle material layer. Therefore, processing marks can be formed on the brittle material layer, and cracks can be prevented from forming on the end face of the brittle material layer.

[0029] It should be noted that, in the method of the present invention, "irradiating the optical functional layer with laser along the predetermined cut-off line of the composite material" means irradiating the optical functional layer with laser along the predetermined cut-off line when viewed from the thickness direction of the composite material (the stacking direction of the optical functional layer, the brittle material layer, and the protective layer). Furthermore, in the method of the present invention, "irradiating the protective layer with laser along the predetermined cut-off line" means irradiating the protective layer with laser along the predetermined cut-off line when viewed from the thickness direction of the composite material (the stacking direction of the optical functional layer, the brittle material layer, and the protective layer). Additionally, "irradiating the brittle material layer with laser from the second processing groove side along the predetermined cut-off line" means irradiating the protective layer with laser from the second processing groove side when viewed from the thickness direction of the composite material (the stacking direction of the optical functional layer, the brittle material layer, and the protective layer).

[0030] Furthermore, in the method of the present invention, "irradiation along the predetermined cut-off line" means irradiating on the predetermined cut-off line, or irradiating at a position near the predetermined cut-off line and parallel to the predetermined cut-off line.

[0031] Furthermore, in the method of the present invention, "the width of the second processing groove" refers to the dimension of the bottom of the second processing groove in a direction orthogonal to the predetermined cut-off line.

[0032] Furthermore, in the method of the present invention, there is no particular limitation on the types of the first and second laser light sources used in the forming process of the processing tank, as long as they are types capable of removing resin by oscillating laser light. However, from the viewpoint of increasing the relative movement speed (processing speed) of the laser relative to the composite material, it is preferable to use a CO2 laser light source or a CO laser light source that oscillates a laser in the infrared region. The first and second laser light sources can be of the same type or different types. In addition, the first and second laser light sources do not necessarily need to be prepared separately; the first laser light source can also be used simultaneously as the second laser light source.

[0033] With a first laser source and a second laser source prepared separately, the first laser source is positioned on the optical functional layer side, and the second laser source is positioned on the protective layer side. After forming a first machining groove in the optical functional layer using the first laser source, a second machining groove is formed in the protective layer using the second laser source. Alternatively, the second machining groove can be formed in the protective layer using the second laser source, and then the first machining groove can be formed in the optical functional layer using the first laser source. Furthermore, the first and second machining grooves can be formed simultaneously using both the first and second laser sources.

[0034] Alternatively, when the first laser source is also used as the second laser source, the first laser source (or the second laser source) can be disposed on the side opposite to either the optical functional layer or the protective layer. After forming the first processing groove in the optical functional layer (or forming the second processing groove in the protective layer) using the first laser source (or the second laser source), the composite material can be flipped so that the first laser source (or the second laser source) is opposite to either the optical functional layer or the protective layer, and the second processing groove in the protective layer (or the first processing groove in the optical functional layer) can be formed using the first laser source (or the second laser source).

[0035] Furthermore, in the method of the present invention, the processing mark formed in the processing mark forming process can be, for example, a toothed through hole along a predetermined cutting line as described in Patent Document 2. In this case, the composite material can be cut by applying an external force along the predetermined cutting line after the processing mark forming process. Methods for applying external force to the composite material include mechanical fracture (bending), heating of the area near the predetermined cutting line using an infrared laser, application using the vibration of an ultrasonic roller, and adsorption and lifting using a suction cup. When heating the area near the predetermined cutting line using an infrared laser, the thermal stress generated in the brittle material layer causes cracking to develop along the predetermined cutting line, connecting the toothed through holes, thereby cutting (severing) the brittle material layer. It should be noted that if resin residue remains at the bottom of the first processing tank, after cutting the brittle material layer by applying external force as described above, the composite material can be cut by further applying mechanical external force, for example, to the optical functional layer. Even if further mechanical forces are applied to the optical functional layer and thus the brittle material layer, at that moment, because the brittle material layer has been truncated, no cracks will form on the end face of the brittle material layer.

[0036] In the method of the present invention, the machining marks formed in the machining mark formation step are not necessarily limited to tooth-shaped through holes. In the machining mark formation step, if the relative movement speed between the laser oscillated by the ultrashort pulse laser source and the brittle material layer along the predetermined cut-off line is set to a small value, or if the repetition frequency of the pulse oscillation of the ultrashort pulse laser source is set to a large value, then a through hole (elongated hole) integrally connected along the predetermined cut-off line will be formed as a machining mark. In this case, the brittle material layer can be cut off even without applying external force along the predetermined cut-off line after the machining mark formation step. However, if resin residue remains at the bottom of the first processing tank, after cutting off the brittle material layer, the composite material can be cut off by applying mechanical external force, for example, to the optical functional layer.

[0037] In the method of the present invention, in order to make the width of the second processing groove formed in the processing groove forming process greater than or equal to the spot diameter of the laser (ultra-short pulse laser) oscillating from the ultra-short pulse laser source at the irradiation position of the brittle material layer in the processing mark forming process, for example, it is advisable to peel off the resin forming the protective layer between each irradiation position after the irradiation positions of the laser oscillating from the second laser source are staggered in a direction orthogonal to the predetermined cut-off line. If the size of the portion of the resin peeled off (the size in the direction orthogonal to the predetermined cut-off line) is greater than or equal to the spot diameter of the ultra-short pulse laser at the irradiation position of the brittle material layer, then the width of the second processing groove can be greater than or equal to the spot diameter of the ultra-short pulse laser at the irradiation position of the brittle material layer.

[0038] That is, preferably in the above-mentioned processing tank forming process, the laser oscillated by the second laser source irradiates the protective layer at the irradiation positions along the predetermined cut-off line in a direction orthogonal to the predetermined cut-off line, and then the resin present between the irradiation positions that forms the protective layer is peeled off, thereby forming the second processing tank.

[0039] According to the preferred method described above (hereinafter, appropriately referred to as the "peeling method"), for example, during the forming process of the processing groove, a laser oscillated by the second laser source can be used to irradiate positions at equal distances in a direction orthogonal to the predetermined cut-off line, thereby peeling off the resin forming the protective layer present therebetween. Thus, after the second processing groove, centered on the predetermined cut-off line in its width direction, is formed, when an ultrashort pulse laser is irradiated along the predetermined cut-off line, the irradiation position of the laser oscillated by the second laser source and the irradiation position of the ultrashort pulse laser will be offset by only 1 / 2 the width of the second processing groove.

[0040] Therefore, even assuming that the output of the laser oscillating from the second laser source is set to a certain extent during the forming process of the processing tank, and that the resin forming the protective layer is removed, exposing the surface of the brittle material layer and causing certain thermal damage, it is not easy for the same part to be irradiated with an ultrashort pulse laser. Therefore, it is not easy to cause cracks to form on the end face of the brittle material layer.

[0041] It should be noted that the removal of the resin forming the protective layer between the irradiation sites can be carried out using a known stripping device.

[0042] In the method of the present invention, the method of making the width of the second processing groove formed in the processing groove forming process greater than or equal to the spot diameter at the irradiation position of the ultrashort pulse laser on the brittle material layer is not limited to the above-described peeling method.

[0043] For example, the following method may be used: In the above-mentioned processing groove forming process, the laser oscillating from the second laser source irradiates the protective layer at the positions of the laser irradiation positions along the cut-off predetermined line in a direction orthogonal to the cut-off predetermined line, thereby forming the second processing groove (hereinafter appropriately referred to as the "offset method").

[0044] When the offset range of the irradiation position of the laser oscillating from the second laser source (the range in the direction orthogonal to the predetermined cut-off line) is greater than or equal to the spot diameter of the ultrashort pulse laser at the irradiation position of the brittle material layer, the width of the second processing groove can be greater than or equal to the spot diameter of the ultrashort pulse laser at the irradiation position of the brittle material layer.

[0045] In this invention, the diameter of the spot at the irradiation location of the brittle material layer by the ultrashort pulse laser is set to, for example, 100 μm.

[0046] Therefore, in the above-mentioned processing tank forming process, it is preferable to remove the resin forming the protective layer in such a way that the width of the second processing tank reaches 100 μm or more, and more preferably to remove the resin forming the protective layer in such a way that the width of the second processing tank reaches 150 μm or more.

[0047] It should be noted that when the spot diameter at the irradiation location of the brittle material layer by the ultrashort pulse laser is 100 μm, the spot diameter on the side of the optical functional layer of the brittle material layer becomes, for example, 1.2 μm after focusing. Furthermore, when the spot diameter at the irradiation location of the brittle material layer by the ultrashort pulse laser is 100 μm, the spot diameter at a location corresponding to the surface of the protective layer (the side opposite to the side of the brittle material layer) becomes, for example, 154 μm.

[0048] Preferably, the protective layer comprises a substrate layer and an adhesive layer disposed on the side of the brittle material layer. In the process of forming the processing groove, the resin forming the protective layer is removed in such a way that a portion of the adhesive layer remains in the thickness direction.

[0049] According to the preferred method described above, in the process of forming the groove, the resin forming the protective layer is removed in such a way that a portion of the adhesive layer remains in the thickness direction. Therefore, the brittle material layer is less susceptible to thermal damage and less prone to cracking at the end face of the brittle material layer.

[0050] As the adhesive layer for forming the protective layer, an acrylic adhesive can be used, but in order to prevent the generation of fumes when the second processing tank of the protective layer is formed during the processing tank forming process, it is preferable to use a urethane adhesive that does not easily generate fumes.

[0051] That is, preferably, the protective layer includes a substrate layer and a urethane adhesive layer disposed on the side of the brittle material layer.

[0052] According to the preferred method described above, dust generation from the adhesive layer of the protective layer can be prevented during the tank forming process. This preferred method is particularly effective when the aforementioned offset method is used in the tank forming process. That is, when the offset method is used, compared to the peeling method, the laser emitted from the second laser source irradiates a larger area of ​​the protective layer, thus reducing the likelihood of dust generation from the adhesive layer of the protective layer. Therefore, the preferred method described above, which prevents dust generation, is particularly effective when the offset method is used.

[0053] The method of the present invention can be adapted, for example, to cases where the brittle material layer comprises glass and the optical functional layer comprises a polarizing film.

[0054] The effects of the invention

[0055] According to the present invention, a composite material having a resin-based optical functional layer laminated on one side of a brittle material layer and a resin-based protective layer laminated on the other side of the brittle material layer can be cut without causing cracks at the end face of the brittle material layer. Attached Figure Description

[0056] Figure 1 The diagram is a cross-sectional view, schematically illustrating a simplified structure of a composite material employing a cutting method according to one embodiment of the present invention.

[0057] Figure 2 This is an explanatory diagram illustrating a simplified sequence of a method for cutting a composite material according to one embodiment of the present invention.

[0058] Figure 3 This is a cross-sectional view that schematically illustrates the simplified sequence of the peeling process in the formation of the processing groove.

[0059] Figure 4 The top view schematically illustrates the stripping method and the brief sequence of the machining groove forming process in the case of cutting the composite material into four rectangular composite material sheets.

[0060] Figure 5 This is a cross-sectional view that schematically illustrates the simplified sequence of the offset method in the process of forming the machining groove.

[0061] Figure 6 The diagram, presented as a top view, schematically illustrates the offset method and the brief sequence of the machining groove forming process in the case where the composite material is cut into four rectangular composite sheets.

[0062] Figure 7 The example shown is a case where the peeling method is used in the process of forming the processing tank.

[0063] Figure 8 As an example, the test conditions and test results are shown in the case of using the offset method in the process of forming the machining groove.

[0064] Symbol Explanation

[0065] 1. Brittle material layer

[0066] 2···Optical Functional Layer

[0067] 3··· Protective layer

[0068] 3a···Substrate layer

[0069] 3b··· Adhesive layer

[0070] 10. Composite Materials

[0071] 11···Machining marks

[0072] 20... First laser source

[0073] 21··· First processing slot

[0074] 30···Second laser source

[0075] 31···Second Machining Tank

[0076] 40. Ultrashort pulse laser source

[0077] D···Spot diameter

[0078] DL··· Cut off the predetermined line

[0079] L1, L2, L3... lasers

[0080] W...width of the second processing slot Detailed Implementation

[0081] Hereinafter, a method for cutting a composite material according to one embodiment of the present invention will be described with appropriate reference to the accompanying drawings.

[0082] <Composition of Composite Materials>

[0083] First, the composition of the composite material using the cutting method of this embodiment will be explained.

[0084] Figure 1 This is a cross-sectional view showing a simplified structure of the composite material using the cutting method of this embodiment.

[0085] It should be noted that, Figure 1 These figures are shown for reference only. It is worth noting that the dimensions, scales, and shapes of components, etc., shown in the figures may sometimes differ from the actual figures. The same applies to other figures.

[0086] like Figure 1 As shown, the composite material 10 has a brittle material layer 1, and is laminated on one side of the brittle material layer 1 (in... Figure 1 The example shown is the lower side) of the resin optical functional layer 2, and the other side (in the case of the brittle material layer 1) is laminated on the other side. Figure 1 In the example shown, the protective layer 3 is composed of layers of resin (top side). The protective layer 3 includes a substrate layer 3a and an adhesive layer 3b disposed on the side of the brittle material layer 1.

[0087] The truncation method of this embodiment is to cut the composite material 10 in the thickness direction (the stacking direction of the optical functional layer 2, the brittle material layer 1, and the protective layer 3). Figure 1 The method of truncation in the vertical direction and the Z direction.

[0088] The brittle material layer 1, the optical functional layer 2, and the protective layer 3 can be stacked by any suitable method. For example, the brittle material layer 1, the optical functional layer 2, and the protective layer 3 can be stacked by a so-called roll-to-roll method. For example, while transporting a long strip of the brittle material layer 1 and a long strip of the optical functional layer 2 in the longitudinal direction (e.g., from... Figure 1 From top to bottom, the optical functional layer 2 consists of a polarizing film, an adhesive, and a release film. It should be noted that... Figure 1(Illustrations of polarizing film, adhesive, and release film omitted) The brittle material layer 1 and the optical functional layer 2 (the body of the optical functional layer 2 and the adhesive) are laminated together by bonding them together with an adhesive (not shown) in a manner that aligns their length directions. Next, while transporting a strip of the laminate of the brittle material layer 1 and the optical functional layer 2, and a strip of the substrate layer 3a of the protective layer 3 in the length direction, they are bonded together with an adhesive layer 3b in a manner that aligns their length directions, thereby laminating the brittle material layer 1, the optical functional layer 2, and the protective layer 3 together. Alternatively, the bodies of the brittle material layer 1 and the optical functional layer 2 can be cut into given shapes and then laminated together with an adhesive. Alternatively, the laminate of the brittle material layer 1 and the optical functional layer 2, and the substrate layer 3a of the protective layer 3 can be cut into given shapes and then laminated together with an adhesive layer 3b.

[0089] Examples of brittle materials used to form the brittle material layer 1 include glass and monocrystalline or polycrystalline silicon. Glass is preferred.

[0090] As for glass, examples based on composition include soda-lime glass, borosilicate glass, aluminosilicate glass, quartz glass, and sapphire glass. Additionally, examples based on alkali content include alkali-free glass and low-alkali glass. The content of alkali metal components (e.g., Na₂O, K₂O, Li₂O) in the glass is preferably 15% by weight or less, more preferably 10% by weight or less.

[0091] The thickness of the brittle material layer 1 is preferably 150 μm or less, more preferably 120 μm or less, and even more preferably 100 μm or less. On the other hand, the thickness of the brittle material layer 1 is preferably 30 μm or more, more preferably 80 μm or more. If the thickness of the brittle material layer 1 is within such a range, roll-to-roll stacking with the optical functional layer 2 can be achieved.

[0092] When the brittle material forming the brittle material layer 1 is glass, the light transmittance of the brittle material layer 1 at a wavelength of 550 nm is preferably 85% or more. When the brittle material forming the brittle material layer 1 is glass, the refractive index of the brittle material layer 1 at a wavelength of 550 nm is preferably 1.4 to 1.65. When the brittle material forming the brittle material layer 1 is glass, the density of the brittle material layer 1 is preferably 2.3 g / cm³. 3 ~3.0g / cm 3 A further preferred value is 2.3 g / cm³. 3 ~2.7g / cm 3 .

[0093] When the brittle material forming the brittle material layer 1 is glass, commercially available glass sheets can be used directly as the brittle material layer 1, or commercially available glass sheets can be ground to the desired thickness. Examples of commercially available glass sheets include: Corning Gorilla Glass "7059", "1737" or "EAGLE2000", Asahi Glass Co., Ltd. "AN100", NHTechno Glass Co., Ltd. "NA-35", Nippon Electric Glass Co., Ltd. "OA-10G", and Schott AG "D263" or "AF45".

[0094] As the main body of the optical functional layer 2, examples include: a single-layer film or a multi-layer film composed of various plastic materials such as acrylic resins (PET, PE, PP, PMMA, etc.), cyclic olefin polymers (COP), cyclic olefin copolymers (COC), polycarbonate (PC), urethane resins, polyvinyl alcohol (PVA), polyimide (PI), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polystyrene (PS), cellulose triacetate (TAC), polyethylene naphthalate (PEN), ethylene-vinyl acetate (EVA), polyamide (PA), silicone resin, epoxy resin, liquid crystal polymer, and foams made of various resins.

[0095] When the main body of the optical functional layer 2 is a multilayer laminated film, various adhesives and bonding agents such as acrylic adhesive, urethane adhesive, and silicone adhesive can be sandwiched between the layers.

[0096] Alternatively, conductive inorganic films such as indium tin oxide (ITO), Ag, Au, and Cu can be formed on the main surface of the optical functional layer 2.

[0097] The truncation method of this embodiment is particularly suitable for situations where the main body of the optical functional layer 2 is a polarizing film, phase difference film, or the like used in a display.

[0098] The thickness of the main body of the optical functional layer 2 is preferably 20-500 μm, more preferably 50-300 μm.

[0099] In this embodiment, as described above, the main body of the optical functional layer 2 is from Figure 1 A laminated film consisting of a polarizing film, an adhesive, and a release film is stacked sequentially from top to bottom. The main body of the optical functional layer 2 is laminated together with the brittle material layer 1 via an adhesive (not shown). In this embodiment, the combination of the main body (polarizing film, adhesive, and release film) of the optical functional layer 2 and the adhesive is referred to as the optical functional layer 2.

[0100] The polarizing film constituting the main body of the optical functional layer 2 has a polarizer and a protective film disposed on at least one side of the polarizer. The thickness of the polarizer is not particularly limited and can be appropriately selected depending on the purpose. The thickness of the polarizer is typically around 1 to 80 μm. In one embodiment, the thickness of the polarizer is preferably 30 μm or less. The polarizer is an iodine-based polarizer. More specifically, the polarizer can be made of a polyvinyl alcohol resin film containing iodine.

[0101] As a method for manufacturing the polarizing mirror constituting the above-mentioned polarizing film, examples include methods 1 and 2 as described below.

[0102] (1) Method 1: A method for stretching and dyeing polyvinyl alcohol resin film monomers.

[0103] (2) Method 2: A method for stretching and dyeing a laminate (i) having a resin substrate and a polyvinyl alcohol resin layer.

[0104] Method 1 is a well-known and commonly used method in the field, and therefore its detailed description is omitted.

[0105] Method 2 preferably includes stretching and dyeing a laminate (i) having a resin substrate and a polyvinyl alcohol resin layer formed on one side of the resin substrate, thereby fabricating a polarizing mirror on the resin substrate. The laminate (i) can be formed by coating the resin substrate with a coating liquid containing polyvinyl alcohol resin and then drying it. Alternatively, the laminate (i) can also be formed by transferring a polyvinyl alcohol resin film onto the resin substrate. Detailed description of Method 2 is described, for example, in Japanese Patent Application Publication No. 2012-73580, which is incorporated herein by reference.

[0106] The protective film constituting the polarizing film is disposed on one or both sides of the polarizer. As a protective film, cellulose triacetate films, acrylic films, cyclic olefin films, polyethylene terephthalate films, etc., can also be used. It should be noted that the polarizing film may further appropriately include a retardation film. The retardation film can have any suitable optical and / or mechanical properties depending on the purpose.

[0107] The release film constituting the main body of the optical functional layer 2 serves to protect the adhesive layer constituting the main body of the optical functional layer 2 until the composite material 10 is supplied for actual use. Examples of materials constituting the release film include: plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester films; porous materials such as paper, cloth, and nonwoven fabrics; mesh; foam sheets; metal foils; and suitable sheets such as laminates thereof. Plastic films are suitable from the perspective of excellent surface smoothness.

[0108] As the adhesive constituting the optical functional layer 2, examples of adhesives that can be used include polyester adhesives, polyurethane adhesives, polyvinyl alcohol adhesives, and epoxy adhesives. In particular, considering the good adhesion, epoxy adhesives are preferred.

[0109] When the adhesive is a thermosetting adhesive, it can achieve peel resistance by curing (solidifying) it through heating. Similarly, when the adhesive is a light-curing adhesive such as an ultraviolet-curing adhesive, it can achieve peel resistance by curing it through exposure to ultraviolet light. Furthermore, when the adhesive is a moisture-curing adhesive, it can react with moisture in the gaseous atmosphere to cure, thus achieving peel resistance even when left to stand.

[0110] As an adhesive, commercially available adhesives can be used, or various curing resins can be dissolved or dispersed in a solvent to prepare an adhesive solution (or dispersion).

[0111] The thickness of the adhesive is preferably less than 10 μm, more preferably 1 to 10 μm, even more preferably 1 to 8 μm, and particularly preferably 1 to 6 μm.

[0112] In this embodiment, the substrate layer 3a of the protective layer 3 is laminated onto the brittle material layer 1 via the adhesive layer 3b. Alternatively, the substrate layer 3a of the protective layer 3 may be made of a self-adhesive film, thereby being laminated onto the brittle material layer 1 without the adhesive layer. From the viewpoint of protecting the brittle material layer 1, it is preferable to laminate it onto the brittle material layer 1 via the adhesive layer 3b as in this embodiment.

[0113] From the viewpoints of inspection and management, the substrate layer 3a can be selected from membrane materials that are isotropic or nearly isotropic. Examples of such membrane materials include transparent polymers such as polyethylene terephthalate (PET) films, polyester resins, cellulose resins, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, and acrylic resins. Among these, polyester resins are preferred. The substrate layer 3a can also be a laminate of one or more membrane materials, or a stretched version of the aforementioned membranes. The thickness of the substrate layer 3a is preferably 35 μm to 100 μm or less, more preferably more than 38 μm but less than 100 μm.

[0114] As the adhesive forming the adhesive layer 3b, an adhesive with a base polymer such as (meth)acrylic polymer, silicone polymer, polyester, polyurethane, polyamide, polyether, fluorinated polymer, or rubber polymer can be appropriately selected. From the viewpoints of transparency, weather resistance, and heat resistance, acrylic adhesives with acrylic polymers as the base polymer are preferred. As will be described later, to prevent the generation of fumes during the formation of the second processing groove 31 of the protective layer 3, a urethane adhesive with a polyurethane base polymer is preferred as the adhesive forming the adhesive layer 3b. The thickness (dry film thickness) of the adhesive layer 3b is determined according to the required adhesion strength. It is typically around 1 to 100 μm, preferably 5 to 50 μm.

[0115] <Methods for cutting composite materials>

[0116] The following describes the cutting method of the composite material 10 having the above-described structure.

[0117] The cutting method of this embodiment includes a groove forming process and a machining mark forming process. Additionally, depending on the need, the cutting method of this embodiment may include a composite material cutting process. Each process will be described in turn below.

[0118] [Machining groove formation process]

[0119] Figure 2 This is an explanatory diagram illustrating a simplified sequence of the truncation method of this embodiment. Figure 2 (a) and (b) are cross-sectional views showing the groove forming process of the cutting method of this embodiment. Figure 2 (c) is a cross-sectional view showing the machining mark formation process of the cutting method of this embodiment. Figure 2 (d) is a cross-sectional view showing the composite material cutting process of the cutting method of this embodiment.

[0120] like Figure 2 As shown in (a), in the process of forming the processing groove, the optical functional layer 2 is irradiated with a laser L1 oscillating from the first laser source 20 along the predetermined cut-off line of the composite material 10, thereby removing the resin forming the optical functional layer 2. As a result, the first processing groove 21 along the predetermined cut-off line is formed.

[0121] exist Figure 2In the example shown, for convenience, the figure illustrates a straight line DL extending along the Y direction in two orthogonal directions (X direction and Y direction) within the plane of the composite material 10, which is a predetermined cutoff line. However, the present invention is not limited to this. For example, various predetermined cutoff lines can be set, such as multiple straight lines DL extending along the X direction and multiple straight lines DL extending along the Y direction, in a grid pattern. Hereinafter, this straight line DL will be referred to as the "predetermined cutoff line DL".

[0122] The truncation line DL can be actually drawn on the composite material 10 as a visually identifiable marker, or its coordinates can be pre-input into a control device (not shown) that controls the relative positional relationship between the laser L1 and the composite material 10 in the XY two-dimensional plane. Figure 2 The cut-off line DL shown is an imaginary line whose coordinates are pre-input into the control device and is not actually drawn on the composite material 10. It should be noted that the cut-off line DL is not limited to a straight line and can also be a curve. The cut-off line DL can be determined according to the application of the composite material 10, thereby cutting the composite material 10 into any shape / size corresponding to the application.

[0123] In this embodiment, the first laser source 20 is a CO2 laser source with a wavelength of 9-11 μm in the infrared region, which is used as the oscillating laser L1.

[0124] However, the present invention is not limited to this. As the first laser source 20, a CO laser source with a wavelength of 5 μm for the oscillating laser L1 can also be used.

[0125] Alternatively, visible light and ultraviolet (UV) pulsed laser sources can also be used as the first laser source 20. Examples of visible light and UV pulsed laser sources include excimer laser sources with wavelengths of 532 nm, 355 nm, 349 nm, or 266 nm (high harmonics of solid-state laser sources using Nd:YAG, Nd:YLF, or YVO4 as the medium), excimer laser sources with wavelengths of 351 nm, 248 nm, 222 nm, 193 nm, or 157 nm, and F2 laser sources with wavelengths of 157 nm for the oscillating laser L1.

[0126] Alternatively, the first laser source 20 can be a pulsed laser source with a wavelength outside the ultraviolet region and a pulse width in the femtosecond or picosecond range, from which the oscillating laser L1 is generated. If the laser L1 oscillated by this pulsed laser source is used, ablation processing based on a multiphoton absorption process can be induced.

[0127] In addition, a semiconductor laser source or a fiber laser source with the wavelength of the oscillating laser L1 in the infrared region can also be used as the first laser source 20.

[0128] As a method of irradiating the laser L1 along the predetermined cut-off line of the composite material 10 (scanning the laser L1), for example, one could consider: placing and fixing (e.g., adsorbing and fixing) the monolithic composite material 10 on an XY dual-axis stage (not shown), and driving the XY dual-axis stage using a control signal from a control device, thereby changing the relative position of the composite material 10 with respect to the laser L1 in the XY two-dimensional plane. Alternatively, one could consider: fixing the position of the composite material 10, and using a galvanometer mirror or a multifaceted mirror driven by a control signal from a control device to deflect the laser L1 oscillating from the first laser source 20, thereby changing the position of the laser L1 irradiating the composite material 10 in the XY two-dimensional plane. Furthermore, one could combine the above-described scanning of the composite material 10 using an XY dual-axis stage with the scanning of the laser L1 using a galvanometer mirror, etc.

[0129] The oscillation mode of the first laser source 20 can be pulsed oscillation or continuous oscillation. The spatial intensity distribution of the laser L1 can be Gaussian or shaped into a flat-top distribution by using diffractive optical elements (not shown) to suppress thermal damage to the brittle material layer 1 other than the target of laser L1 removal. The polarization state of the laser L1 is not limited and can be any polarization state among linearly polarized light, circularly polarized light, and randomly polarized light.

[0130] By irradiating the optical functional layer 2 with laser L1 along the predetermined cut-off line DL of the composite material 10, the resin in the resin forming the optical functional layer 2 that has been irradiated with laser L1 experiences a localized temperature rise due to infrared light absorption, resulting in resin scattering. This removes the resin from the composite material 10, forming a first processing groove 21 in the composite material 10. To prevent the scattered resin removed from the composite material 10 from re-adhering to the composite material 10, a dust collection mechanism is preferably provided near the predetermined cut-off line DL. To prevent the width of the first processing groove 21 from becoming too large, it is preferable to focus the laser L1 such that the spot diameter at the irradiation position of the optical functional layer 2 (the spot diameter on the side of the optical functional layer 2 opposite to the side of the brittle material layer 1) is 300 μm or less, and more preferably, the laser L1 is focused such that the spot diameter is 200 μm or less.

[0131] The diameter of the laser spot L1 at the irradiation position of the optical functional layer 2 can be set to approximately 150 μm. In this case, the diameter of the laser spot on the brittle material layer 1 side of the optical functional layer 2 is focused to become, for example, 30 to 40 μm. This allows the formation of a first processing groove 21 with a width (the dimension of the bottom of the first processing groove 21 in the direction orthogonal to the predetermined truncation line DL) of 30 to 40 μm.

[0132] The width of the first processing groove 21 is, for example, 100 μm or less, preferably 50 μm or less.

[0133] It should be noted that, according to the present inventors, in the case of a resin removal method based on the principle that the resin irradiated by laser L1 experiences a local temperature rise due to infrared light absorption, regardless of the type of resin or the layer structure of the optical functional layer 2, the input energy required to form the first processing tank 21 can be roughly estimated based on the thickness of the optical functional layer 2. Specifically, the input energy required to form the first processing tank 21, expressed by the following formula (1), can be estimated based on the thickness of the optical functional layer 2 using the following formula (2).

[0134] Input energy [mJ / mm] = Average power of laser L1 [mW] / Processing speed [mm / sec] ···(1)

[0135] Input energy [mJ / mm] = 0.5 × thickness of optical functional layer 2 [μm] ···(2)

[0136] The actual input energy is preferably set to 20% to 180% of the input energy estimated by the above formula (2), and more preferably to 50% to 150%. This margin in the estimated input energy is taken into account that the input energy required to form the first processing groove 21 will vary depending on the different thermophysical properties of the resin forming the optical functional layer 2, such as the light absorption rate (light absorption rate at the wavelength of laser L1) and the resin's melting point / decomposition point. Specifically, for example, a sample of the composite material 10 prepared using the cutting method of this embodiment can be tested to form the first processing groove 21 in the optical functional layer 2 of the sample using multiple input energies within the above-mentioned preferred range to determine a suitable input energy.

[0137] In addition, such as Figure 2 As shown in (b), in the process of forming the processing groove, the protective layer 3 is irradiated with a laser L2 oscillating from the second laser source 30 along the predetermined cut-off line of the composite material 10, thereby removing the resin forming the protective layer 3. This forms a second processing groove 31 along the predetermined cut-off line (see reference). Figure 2 (c) When forming the second processing groove 31, in this embodiment, a peeling method or an offset method is used, the details of which will be described later.

[0138] In this embodiment, the second processing groove 31 is formed after the first processing groove 21 is formed. However, the present invention is not limited to this, and the first processing groove 21 may be formed after the second processing groove 31 is formed. Additionally, as... Figure 2 As shown, if a first laser light source 20 and a second laser light source 30 are prepared separately, a first processing groove 21 and a second processing groove 31 can also be formed simultaneously.

[0139] In this embodiment, the second laser source 30 is a CO2 laser source of the same type as the first laser source 20. However, the present invention is not limited to this, and other laser sources such as CO laser sources may also be used for the first laser source 20 in the same manner as described above. The second laser source 30 may be of the same type as the first laser source 20, or it may be of a different type. As for the method of irradiating laser L2 along the predetermined cutoff line DL (the method of scanning laser L2 in a relatively symmetrical manner), the same method described above for laser L1, using an XY dual-axis stage, galvanometer mirror, etc., may be employed.

[0140] Laser L2 is used to focus the light so that the diameter of the light spot at the irradiation position of the protective layer 3 (the diameter of the light spot on the side of the protective layer 3 opposite to the side of the brittle material layer 1) reaches, for example, 120 to 130 μm. As a result, a groove with a width of 20 to 30 μm at the bottom can be formed.

[0141] The second machining groove 31 is made so that its width W (refer to) Figure 2 (c) is the diameter D of the laser spot at the irradiation location of the brittle material layer 1 by the laser L3 oscillating from the ultrashort pulse laser source 40 in the machining mark formation process described later (refer to...). Figure 2 (c)) The above methods are used to form it.

[0142] Specifically, in this embodiment, the width W of the second processing groove 31 is preferably 100 μm or more, more preferably 150 μm or more. The upper limit of the width W of the second processing groove 31 is, for example, 1000 μm or less, preferably 500 μm or less, and more preferably 300 μm or less.

[0143] As described above, the width W of the second processing groove 31 is preferably 100 μm or more, and is preferably greater than the width of the first processing groove 21, which is preferably 100 μm or less.

[0144] exist Figure 2 In the example shown, a first laser source 20 is configured on the side opposite to the optical functional layer 2, and a second laser source 30, which is different from the first laser source 20, is configured on the side opposite to the protective layer 3. However, the present invention is not limited to this, and the first laser source 20 can also be used as the second laser source 30 at the same time.

[0145] When the first laser source 20 is also used as the second laser source 30, for example, as Figure 2As shown in (a), a first laser source 20 (or a second laser source 30) is disposed on the side opposite to the optical functional layer 2. A first processing groove 21 is formed in the optical functional layer 2 using the first laser source 20 (or the second laser source 30). Then, the composite material 10 is flipped up and down using a known flipping mechanism so that the first laser source 20 (or the second laser source 30) is opposite to the protective layer 3. A second processing groove 31 is then formed in the protective layer 3 using the first laser source 20 (or the second laser source 30). Alternatively, as... Figure 2 As shown in (b), a first laser source 20 (second laser source 30) is disposed on the side opposite to the protective layer 3. The first laser source 20 (second laser source 30) is used to form a second processing groove 31 in the protective layer 3. Then, the composite material 10 is flipped up and down using a known flipping mechanism so that the first laser source 20 (second laser source 30) is opposite to the optical functional layer 2. The first processing groove 21 is formed in the optical functional layer 2 using the first laser source 20 (second laser source 30).

[0146] It should be noted that, in the process of forming the processing tank, as a preferred method, the resin forming the optical functional layer 2 can be removed such that a portion of the optical functional layer 2 remains as residue in the thickness direction. Furthermore, in this embodiment, as a preferred method, the resin forming the protective layer 3 is removed such that a portion of the adhesive layer 3b of the protective layer 3 remains as residue in the thickness direction. For either the optical functional layer 2 or the protective layer 3, the thickness of the residue is preferably 1 to 30 μm, more preferably 1 to 10 μm.

[0147] In this way, by removing the resin in a manner that leaves residue, compared to the case where the resin forming the optical functional layer 2 and the protective layer 3 is completely removed along the predetermined cut line DL, the advantages of reduced thermal damage to the brittle material layer 1 and less likelihood of cracks forming on the end face of the brittle material layer 1 can be obtained.

[0148] [Machining Mark Formation Process]

[0149] like Figure 2 As shown in (c), in the machining mark formation process, after the machining groove formation process, the brittle material layer 1 is removed by irradiating the brittle material layer 1 with a laser (ultra-short pulse laser) L3 oscillating (pulse oscillation) from the ultra-short pulse laser source 40 along the predetermined cut-off line DL from the side of the second machining groove 31. This process forms a machining mark 11 along the predetermined cut-off line DL.

[0150] As for the method of irradiating laser L3 along the predetermined cut-off line DL (the method of scanning laser L3 relatively), the same method as the method of irradiating laser L1 along the predetermined cut-off line DL can be used, so detailed description is omitted here.

[0151] The brittle material forming the brittle material layer 1 can be removed by utilizing the filamentation phenomenon of laser L3 oscillating from the ultrashort pulse laser source 40, or by applying a multifocal optical system (not shown) or a Bessel beam optical system (not shown) to the ultrashort pulse laser source 40.

[0152] It should be noted that the application of filamentation phenomena using ultrashort pulse lasers and the use of multifocal optical systems or Bessel beam optical systems to ultrashort pulse laser sources has been described in Non-Patent Literature 1. Furthermore, Trumpf GmbH of Germany sells products related to glass processing using multifocal optical systems in ultrashort pulse laser sources. As such, the application of filamentation phenomena using ultrashort pulse lasers and the use of multifocal optical systems or Bessel beam optical systems to ultrashort pulse laser sources is well-known, therefore detailed explanations are omitted here.

[0153] In the machining mark forming process of this embodiment, the machining mark 11 formed can be formed as, for example, a toothed through hole along a predetermined cutting line DL as described in Patent Document 2. The spacing of the through holes along the predetermined cutting line DL is determined based on the repetition frequency of the pulse oscillation and the relative movement speed (processing speed) of the laser L3 relative to the composite material 10. In order to facilitate and stably perform the composite material cutting process described later, the spacing of the through holes is preferably set to 10 μm or less, more preferably 5 μm or less. The diameter of the through holes is mostly formed to be 5 μm or less.

[0154] However, it should be noted that the machining mark 11 is not limited to a tooth-shaped through hole along the predetermined cut-off line DL. When the relative movement speed between the laser L3 oscillated by the ultrashort pulse laser source 40 and the brittle material layer 1 along the predetermined cut-off line DL is set to be small, or when the repetition frequency of the pulse oscillation of the ultrashort pulse laser source 40 is set to be large, a through hole (elongated hole) integrally connected along the predetermined cut-off line DL can be formed as the machining mark 11.

[0155] When the brittle material forming the brittle material layer 1 is glass, the wavelength of the laser L3 oscillated by the ultrashort pulse laser source 40 is preferably 500 nm to 2500 nm, exhibiting high transmittance. To effectively induce nonlinear optical phenomena (multiphoton absorption), the pulse width of the laser L3 is preferably 100 picoseconds or less, more preferably 50 picoseconds or less. The oscillation mode of the laser L3 can be single-pulse oscillation or burst-mode multi-pulse oscillation.

[0156] like Figure 2As shown in (c), the diameter D of the laser spot at the irradiation position of the brittle material layer 1 by the laser L3 can be set to, for example, 100 μm. As described above, the width W of the second processing groove 31 reaches or exceeds this diameter D.

[0157] It should be noted that a cleaning process may further be included, which removes resin residues forming the protective layer 3 by cleaning the second processing tank 31 formed in the processing tank forming process using various wet or dry methods prior to the processing mark forming process. If the resin residues forming the protective layer 3 are removed in the cleaning process, even if the brittle material layer 1 is irradiated with laser L3 oscillating from the ultrashort pulse laser source 40 from the second processing tank 31 side in the processing mark forming process, the laser L3 will not be affected by the resin residues, and a more suitable processing mark 11 can be formed in the brittle material layer 1.

[0158] [Composite Material Cutting Process]

[0159] like Figure 2 As shown in (d), in the composite material cutting process, an external force is applied along the predetermined cutting line DL after the machining mark formation process, thereby cutting the composite material 10. Figure 2 In the example shown in (d), composite material 10 is cut into composite material sheets 10a and 10b.

[0160] When the machining mark 11 formed in the machining mark forming process is a toothed through hole along the predetermined cut-off line DL, and the resin forming the optical functional layer 2 is removed in such a way that a portion of the optical functional layer 2 remains as residue (residue remains at the bottom of the first processing tank 21), the composite material cutting process becomes particularly necessary. When the machining mark 11 is a through hole (elongated hole) integrally connected along the predetermined cut-off line DL, and no residue remains at the bottom of the first processing tank 21, the composite material 10 can be cut off simultaneously with the machining mark forming process, so the composite material cutting process is not necessarily required.

[0161] Examples of methods for applying external force to the composite material 10 include mechanical fracture (bending), heating of the area near the cut-off line DL using an infrared laser, application of force by vibration of an ultrasonic roller, and adsorption and lifting by a suction cup.

[0162] Hereinafter, in the process of forming the processing groove of the cutting method of this embodiment, the peeling method and the offset method used in forming the second processing groove 31 will be described in sequence.

[0163] (Stripping method)

[0164] Figure 3 This is a cross-sectional view schematically illustrating the simplified sequence of the peeling method in the process of forming the machining groove. The peeling method is according to... Figure 3 (a), (b), and (d) are executed in sequence. It should be noted that... Figure 3 (c) is Figure 3 (b) An enlarged view of the area enclosed by the dashed line C.

[0165] like Figure 3 As shown in (a) and (b), in the stripping method, the laser L2 oscillated by the second laser source 30 is positioned to irradiate the protective layer 3 in a direction orthogonal to the predetermined cut-off line DL (in... Figure 3 In the example shown, the illumination positions are staggered in the X direction. Figure 3 (a) shows the position of A1. Figure 3 (b) Position A2) is irradiated with laser L2 along the predetermined cut-off line DL to the protective layer 3. Specifically, in this embodiment, laser L2 oscillated by the second laser source 30 is irradiated at positions A1 and A2 that are equidistant from each other in the direction orthogonal to the predetermined cut-off line DL (X direction). As a result, processing grooves 31a and 31b are formed at each irradiation position A1 and A2. The separation distance between the processing grooves 31a and 31b in the X direction (the separation distance between each irradiation position A1 and A2) is set as the spot diameter D of the ultrashort pulse laser L3 at the irradiation position of the brittle material layer 1 in the processing mark formation process (refer to...). Figure 2 (c) and above.

[0166] It should be noted that, as described above, in this embodiment, as a preferred method, the resin forming the protective layer 3 is removed by irradiating the protective layer 3 with laser L2, thereby leaving a portion of the adhesive layer 3b of the protective layer 3 as residue (see reference). Figure 3 (c)). As described above, the thickness T of the residue is preferably 1 to 30 μm, more preferably 1 to 10 μm.

[0167] Next, as Figure 3 As shown in (d), in the stripping method, the second processing groove 31 is formed by stripping the resin forming the protective layer 3 present between each irradiation position A1, A2. The resin stripping can be performed using a known stripping device. As described above, the separation distance between processing grooves 31a, 31b is greater than or equal to the spot diameter D of the ultrashort pulse laser L3; therefore, the width W of the second processing groove 31 (refer to...) Figure 2 (c) is also greater than D, which is the spot diameter of the ultrashort pulse laser L3.

[0168] It should be noted that if the resin forming the protective layer 3 between each irradiation position A1 and A2 is peeled off using a stripping method, then as according to Figure 3As can also be seen in (c) or (d), although a portion of the adhesive layer 3b remains as residue in the thickness direction near each irradiation position A1, A2, it is expected that in other parts, the protective layer 3 containing the adhesive layer 3b will peel off entirely, exposing the surface of the brittle material layer 1.

[0169] Based on the stripping method described above, if an ultrashort pulse laser L3 (refer to) is irradiated on the predetermined cut-off line DL... Figure 2 (c)) The irradiation positions A1, A2 of the laser L2 oscillated by the second laser source 30 are offset from the irradiation position of the ultrashort pulse laser L3 by only 1 / 2 of the width W of the second processing groove 31.

[0170] Therefore, even assuming that the output of the laser L2 oscillated by the second laser source 30 is set to a large value during the forming process of the processing tank, and that the resin forming the protective layer 3 is removed, exposing the surface of the brittle material layer 1 and causing certain thermal damage, it is not easy for the ultra-short pulse laser L3 to be irradiated in the same location. Therefore, it is not easy for cracks to be generated on the end face of the brittle material layer 1.

[0171] Figure 4 This is a top view schematically illustrating the simplified sequence of the peeling method and the machining mark formation process in the process of forming a groove when the composite material 10 is cut into four rectangular composite material sheets. Figure 4 (a) to (c) show a brief sequence of the stripping process. Figure 4 (d) shows a simplified sequence of the machining mark formation process. It should be noted that... Figure 4 For convenience, the second laser source 30 and the ultrashort pulse laser source 40 are shown in perspective.

[0172] like Figure 4 As shown in (a), in the stripping method, the irradiation positions of the protective layer 3 by the laser L2 oscillated by the second laser source 30 are staggered in a direction orthogonal to the predetermined cut-off line DL, and the laser L2 irradiates the protective layer 3 along the predetermined cut-off line DL at each irradiation position. Specifically, in Figure 4 In the example shown in (a), only the width W of the second machining groove 31 (refer to) is used compared to the truncation predetermined line DL. Figure 2 (c) The laser L2 is irradiated at a position offset inward from 1 / 2 of the position (indicated by the solid line). Figure 4 The parts indicated by symbols 31a and 31b in (a) are equivalent to Figure 3 The machining grooves 31a and 31b are shown.

[0173] Next, in the stripping process, the second processing groove 31 is formed by stripping the resin that forms the protective layer 3 between each irradiation position. Figure 4(b) shows the resin that forms the protective layer 3 after peeling. Figure 4 (c) shows the peeled composite material 10. Figure 4 In the example shown in (b), not only the resin present between each irradiation position forming the protective layer 3 (present in...) Figure 4 (b) The resin in the cross-shaped area was peeled off, and at the same time the resin forming the protective layer 3 on the outside of the irradiation position was also peeled off.

[0174] Next, as Figure 4 As shown in (d), in the process of forming a machining mark, an ultra-short pulse laser L3 oscillated by an ultra-short pulse laser source 40 is irradiated on the predetermined cut line DL.

[0175] Thus (or by further performing a composite material cutting process), it is possible to cut the composite material into four rectangular pieces.

[0176] (Offset method)

[0177] Figure 5 This is a cross-sectional view schematically illustrating the simplified sequence of the offset method in the process of forming the machining groove. The offset method is based on... Figure 5 Execute in the order of (a) to (d).

[0178] like Figure 5 As shown in (a) to (c), in the offset method, the laser L2 oscillated by the second laser source 30 is positioned to irradiate the protective layer 3 in a direction orthogonal to the predetermined cutoff line DL (in... Figure 5 In the example shown, the X-direction is staggered sequentially at each irradiation position. Figure 5 (a) shows the position of B1. Figure 5 (b) shows the location of B2, and Figure 5 (c) Position B3) irradiates the protective layer 3 with laser L2 along the predetermined cut-off line DL. Specifically, in this embodiment, laser L2 oscillated by the second laser source 30 is sequentially and staggered at positions B1 to B3, which are equidistant from the predetermined cut-off line DL in a direction orthogonal to the predetermined cut-off line DL (X direction), with a given spacing (e.g., a spacing of about 30 μm, the same size as the spot diameter of laser L2). As a result, the width of the processing groove 31c formed at each irradiation position increases sequentially, eventually as shown in the figure. Figure 5 (d) shows the formation of the second processing groove 31. The offset range of the irradiation positions of laser L2 (the separation distance between irradiation positions B1 and B3) is set to the spot diameter D (refer to) at the irradiation position of the ultrashort pulse laser L3 on the brittle material layer 1 during the processing mark formation process. Figure 2 (c) and above, the width W of the second machining groove 31 (refer to) Figure 2(c) The spot diameter D of the ultrashort pulse laser L3 is above that of the laser.

[0179] It should be noted that, similarly in the offset method, as a preferred approach, the resin forming the protective layer 3 is removed by irradiating the protective layer 3 with laser L2, thereby leaving a portion of the adhesive layer 3b in the thickness direction as residue. Especially when using the offset method, compared to the peeling method, the laser L2 oscillated by the second laser source 30 irradiates a larger area of ​​the protective layer 3, thus placing the brittle material layer 1 in a position susceptible to thermal damage. Therefore, leaving a portion of the adhesive layer 3b as residue in the thickness direction is particularly effective when using the offset method.

[0180] Furthermore, when using the offset method, compared to the peeling method, the laser L2 oscillated by the second laser source 30 irradiates a larger area of ​​the protective layer 3, thus making it easier for dust to be generated from the adhesive layer 3b of the protective layer 3. Therefore, when using the offset method, in order to prevent dust generation, it is preferable to make the adhesive layer 3b a urethane adhesive layer.

[0181] Figure 6 This is a top view schematically illustrating the offset method and the simplified sequence of the machining groove forming process in the case where the composite material 10 is cut into four rectangular composite material sheets. Figure 6 (a) shows a brief sequence of the offset method. Figure 6 (b) illustrates a simplified sequence of the machining mark formation process. It should be noted that... Figure 6 For convenience, the second laser source 30 and the ultrashort pulse laser source 40 are shown in perspective.

[0182] like Figure 6 As shown in (a), in the offset method, the irradiation positions of the laser L2 oscillated by the second laser source 30 onto the protective layer 3 are staggered sequentially in a direction orthogonal to the predetermined cutoff line DL, irradiating the protective layer 3 with laser L2 along the predetermined cutoff line DL at each irradiation position. Specifically, in Figure 6 In the example shown in (a), only the width W of the second machining groove 31 (refer to) is used compared to the truncation predetermined line DL. Figure 2 (c) The laser L2 is irradiated in a range that is staggered inward and outward at half the distance from the center (indicated by solid lines), causing the width of the machining groove 31c formed at each irradiation position to increase sequentially. Thus, as... Figure 6 As shown in (b), a second processing groove 31 can be formed (in Figure 6 (b) shows the area without a shading line.

[0183] Next, as Figure 6As shown in (b), in the process of forming a machining mark, an ultra-short pulse laser L3 oscillated by an ultra-short pulse laser source 40 is irradiated on the predetermined cut line DL.

[0184] Thus (or by further performing a composite material cutting process), it is possible to cut the composite material into four rectangular pieces.

[0185] According to the cutting method of this embodiment described above, in the processing groove forming process, by removing the resin forming the optical functional layer 2 and the resin forming the protective layer 3, a first processing groove 21 and a second processing groove 31 are formed along the predetermined cutting line DL. Then, in the processing mark forming process, by removing the brittle material forming the brittle material layer 1 from the second processing groove 31 side, a processing mark 11 is formed along the same predetermined cutting line DL. Since the second processing groove 31 formed in the processing groove forming process is formed with a width W equal to or greater than the spot diameter D at the irradiation position of the brittle material layer 1 by the laser (ultra-short pulse laser) L3 oscillating from the ultra-short pulse laser source 40 in the processing mark forming process, the brittle material layer 1 can be cut off without causing cracks to form on the end face of the brittle material layer 1.

[0186] Hereinafter, an example of the test results of cutting the composite material 10 using the cutting method of this embodiment (Examples 1 to 5) and the cutting method of comparative examples (Comparative Examples 1 and 2) will be described.

[0187] Figure 7 The following is an example of the main test conditions and test results when the peeling method is used in the forming process of the processing tank. Figure 8 The example shown is a case where the offset method was used in the formation of the machining groove, and the main test conditions and test results are presented as an embodiment.

[0188] <Example 1>

[0189] [Fabrication of Optical Functional Layer 2]

[0190] As a thermoplastic resin substrate, one side of the resin substrate was corona treated using a strip of amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) with a glass transition temperature (Tg) of about 75 °C.

[0191] On the other hand, 13 parts by weight of potassium iodide were added to 100 parts by weight of a PVA resin obtained by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a 9:1 ratio, and the resulting mixture was dissolved in water to prepare a PVA aqueous solution (coating solution).

[0192] Then, the above-mentioned PVA aqueous solution was coated on the corona-treated surface of the above-mentioned resin substrate and dried at 60°C, thereby forming a PVA resin layer with a thickness of 13μm and producing a laminate.

[0193] The laminate prepared as described above was stretched unidirectionally along the longitudinal direction (length direction) to 2.4 times in an oven at 130°C (assisted stretching treatment in a gas atmosphere).

[0194] Next, the uniaxially stretched laminate is immersed in an insoluble bath at 40°C (an aqueous solution of boric acid prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) for 30 seconds (insoluble treatment).

[0195] Next, the above-mentioned laminate was immersed in a staining bath at 30°C (an iodine aqueous solution prepared by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) for 60 seconds, while the concentration was adjusted (staining treatment) so that the monomer transmittance (Ts) of the final polarizer reached the desired value.

[0196] Next, the above-mentioned laminate was immersed in a crosslinking bath (an aqueous solution of boric acid prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (crosslinking treatment).

[0197] Next, the above-mentioned laminate was immersed in a boric acid aqueous solution (boric acid concentration 4% by weight, potassium iodide concentration 5% by weight) at a liquid temperature of 70°C, and simultaneously subjected to unidirectional stretching (stretching treatment in aqueous solution) between rollers with different circumferential speeds along the longitudinal direction (length direction) to achieve a total stretching ratio of 5.5 times.

[0198] Next, the above-mentioned laminate is immersed in a cleaning bath at a liquid temperature of 20°C (an aqueous solution of 100 parts by weight of water and 4 parts by weight of potassium iodide) (cleaning treatment).

[0199] Finally, while drying the above-mentioned laminate in an oven at approximately 90°C, it is brought into contact with a stainless steel heating roller at a surface temperature of approximately 75°C (drying shrinkage treatment).

[0200] As described above, a polarizer with a thickness of about 5 μm was formed on a resin substrate, thereby creating a laminate having a resin substrate / polarizer structure.

[0201] Next, an acrylic protective film (thickness: 40 μm) was laminated onto one side of the polarizer constituting the above-mentioned laminate (the side opposite to the resin substrate side) to create a polarizing film. Then, the resin substrate was peeled off from the polarizing film, and a polyethylene terephthalate release film (thickness: 38 μm) was laminated onto the peeled surface using an acrylic adhesive (thickness: 20 μm), thereby creating the main body of the optical functional layer 2.

[0202] In addition, as an adhesive, an epoxy adhesive was prepared by combining 70 parts by weight of CELLOXIDE 2021P (manufactured by CELLOXIDE 2021P, manufactured ...

[0203] The combination of the main body of the optical functional layer 2 and the adhesive described above constitutes the optical functional layer 2.

[0204] [Fabrication of the laminate of brittle material layer 1 and optical functional layer 2]

[0205] As the brittle material layer 1, a glass film (manufactured by Nippon Electric Glass Co., Ltd., trade name "OA-10G", thickness: 100μm) was prepared.

[0206] Next, the brittle material layer 1 and the main body of the optical functional layer 2 are bonded together using the adhesive. At this time, the main body of the optical functional layer 2 is configured such that the acrylic protective film forms the side facing the brittle material layer 1. Next, the adhesive is irradiated with ultraviolet light (500 mJ / cm²) using a high-pressure mercury lamp. 2 The adhesive was cured to create a laminate of a brittle material layer 1 and an optical functional layer 2. The cured adhesive had a thickness of 5 μm.

[0207] [Fabrication of Composite Material 10]

[0208] Next, as Figure 7 As shown, a surface protective film (manufactured by Nitto Denko Corporation, trade name "RP207") with an acrylic adhesive layer was prepared as protective layer 3.

[0209] The substrate layer 3a of the protective layer 3 is formed from an untreated polyethylene terephthalate film (manufactured by Mitsubishi Chemical Polyester Co., Ltd., DIAFOIL T100#38) with a thickness of 38 μm.

[0210] Furthermore, the adhesive layer 3b of the protective layer 3 was prepared as follows. First, 100 parts by weight of 2-ethylhexyl acrylate and 4 parts by weight of 2-hydroxyethyl acrylate were copolymerized in ethyl acetate to achieve a monomer base of 35%, resulting in a solution containing an acrylic polymer with a weight average molecular weight of 600,000. Next, 4 parts by weight of an isocyanate crosslinking agent (Coronate HX, manufactured by Nippon Polyurethane Kogyo Co., Ltd.) having an isocyanurate ring was added to this solution relative to 100 parts by weight of the acrylic polymer (dry weight), and ethyl acetate was further added to prepare an adhesive solution with a solids concentration adjusted to 20%. Finally, the adhesive solution was coated onto the substrate layer 3a to achieve a dry film thickness of 20 μm, and dried at 140°C for 2 minutes to form the adhesive layer 3b.

[0211] The protective layer 3 (RP207) comprises a substrate layer 3a and an adhesive layer 3b as described above. Then, the protective layer 3 and the brittle material layer 1 of the laminate with the brittle material layer 1 and the optical functional layer 2 are bonded together via the adhesive layer 3b of the protective layer 3, thereby producing the composite material 10.

[0212] [Machining groove forming process (forming of the first machining groove 21)]

[0213] After the composite material 10, as described above, is monolithically formed, a first processing groove 21 is formed in the optical functional layer 2. Specifically, a laser processing apparatus equipped with an optical system and control device for controlling the scanning of the first laser source 20 and the laser L1 is used. This apparatus employs a TLSU series laser source (9.4 μm oscillation wavelength, 12.5 kHz pulse oscillation repetition frequency, and 250 W laser L1 power) manufactured by Takei Electric Co., Ltd. The output of the laser L1 oscillated by the first laser source 20 is set to 11.8 W. A focusing lens is used to focus the laser light into a spot with a diameter of 150 μm at the irradiation position of the optical functional layer 2. The optical functional layer 2 is irradiated along the predetermined cut-off lines (multiple predetermined cut-off lines set in a grid pattern) DL of the composite material 10. The relative moving speed (processing speed) of the laser L1 relative to the composite material 10 is set to 400 mm / sec. As a result, the resin forming the optical functional layer 2 is removed, and the first processing groove 21 along the predetermined cut-off lines DL is formed. At this time, the resin is removed in such a way that a portion of the resin forming the optical functional layer 2 remains as residue (thickness: 10-20 μm) at the bottom of the first processing tank 21.

[0214] [Machining groove forming process (forming the second machining groove 31)]

[0215] Next, a second processing groove 31 is formed on the protective layer 3. Specifically, similar to the formation of the first processing groove 21, a laser processing apparatus equipped with an optical system and control device for controlling the scanning of the second laser source 30 and the laser L2 is used, such as the TLSU series (CO2 laser source with an oscillation wavelength of 9.4 μm, a pulse oscillation repetition frequency of 12.5 kHz, and a laser L2 power of 250 W) manufactured by Takei Electric Co., Ltd. Figure 7 As shown, the output of laser L2, oscillating from the second laser source 30, was set to 10.5W. A focusing lens was used to focus the laser beam into a spot diameter of 120–130 μm at the irradiation position of the protective layer 3. The protective layer 3 was irradiated along the predetermined cut-off lines (set as multiple lattice-shaped predetermined cut-off lines) DL of the composite material 10. The relative moving speed (processing speed) of laser L2 relative to the composite material 10 was set to 400 mm / sec. Then, by employing a peeling method, such as… Figure 7 A second processing groove 31 with a width of 200 μm was formed as shown. It should be noted that when the protective layer 3 is irradiated with laser L2, as... Figure 7 As shown, resin was removed at the irradiation site in a manner that prevented a portion of the resin forming the protective layer 3 from remaining as residue (thickness: 0 μm).

[0216] [Machining Mark Formation Process]

[0217] Following the aforementioned groove formation process, a machining mark formation process was performed. Specifically, an ultrashort pulse laser source 40 with an oscillation wavelength of 1064 nm, a pulse width of 10 picoseconds for laser L3, a pulse oscillation repetition frequency of 50 kHz, and an average power of 10 W was used. The laser L3 oscillated by the ultrashort pulse laser source 40 was irradiated onto the brittle material layer 1 of the composite material 10 from the side of the second groove 31 via a multifocal optical system. The spot diameter D at the irradiation position of laser L3 on the brittle material layer 1 was set to 100 μm. The relative moving speed (processing speed) of laser L3 relative to the composite material 10 was set to 100 mm / sec, and laser L3 was scanned along the predetermined cut-off line DL, resulting in the formation of tooth-shaped through holes (approximately 1 to 2 μm in diameter) with a spacing of 2 μm as machining marks 11.

[0218] [Composite Material Cutting Process]

[0219] Following the aforementioned machining mark formation process, a composite material cutting process was performed. Specifically, a laser processing apparatus equipped with an optical system and control device for controlling the CO2 laser source and laser scanning was used. The apparatus employed was an MLG-9300 (oscillation wavelength 10.6 μm, laser power 30 W) manufactured by Keyence Co., Ltd. The output of the laser oscillated from the laser source was set to 80% (i.e., output 24 W), and a focusing lens was used to focus the light into a spot diameter of 0.7 mm (at which point the energy density was 62 W / m²). 2 The brittle material layer 1 was irradiated from the protective layer 3 side along the predetermined cut line DL of the composite material 10. At this time, the relative moving speed of the laser relative to the composite material 10 was set to 500 mm / sec.

[0220] Finally, applying a mechanical force to the composite material 10 cuts off the resin residue remaining at the bottom of the first processing tank 21 after the processing tank forming process, thus cutting off the composite material 10.

[0221] The end face of the brittle material layer 1 of the composite material 10 (composite material sheet) after being cut using the cutting method of Example 1 was visually observed, and the results are as follows: Figure 7 As shown, the brittle material layer 1 can be cut off without problems and without cracks.

[0222] <Example 2>

[0223] like Figure 7 As shown, when forming the second processing groove 31, the output of the laser L2 oscillating from the second laser source 30 was set to 8.0W, and the resin was removed at the irradiation position in such a way that a portion of the resin (adhesive layer 3b) forming the protective layer 3 remained as residue (thickness: 10μm). Apart from this, the composite material 10 was cut off under the same conditions as in Example 1.

[0224] The end face of the brittle material layer 1 of the composite material 10 (composite material sheet) after being cut using the cutting method of Example 2 was visually observed, and the results are as follows: Figure 7 As shown, the brittle material layer 1 can be cut off without problems and without cracks.

[0225] <Comparative Example 1>

[0226] When forming the second processing groove 31, the protective layer 3 was irradiated only once with laser L2 oscillated by the second laser source 30 on the cut-off predetermined lines (set as multiple cut-off predetermined lines in a grid pattern) DL of the composite material 10 (without using a peeling method). Except for this, the cut-off of the composite material 10 was attempted under the same conditions as in Example 1. Figure 7As shown, the width of the second processing groove 31 formed in Comparative Example 1 is 30 μm, which is smaller than the spot diameter D (100 μm) at the irradiation position of the brittle material layer 1 by the laser L3 oscillating from the ultrashort pulse laser source 40 during the processing mark formation process.

[0227] like Figure 7 As shown, in the cutting method of Comparative Example 1, no processing mark 11 was formed through the brittle material layer 1, and the composite material 10 was not cut off.

[0228] <Example 3>

[0229] Except for the aspects shown in (1) to (3) below, composite material 10 was made under the same conditions as in Example 1 and then cut off.

[0230] (1) As Figure 8 As shown, a surface protective film (manufactured by Nitto Denko Corporation, trade name "AW700EC") with a urethane adhesive layer is prepared as protective layer 3.

[0231] The substrate layer 3a of the protective layer 3 is formed from a substrate "Lumirror S10" (38 μm thick, manufactured by Toray Industries, Inc.) made of polyester resin.

[0232] Furthermore, the adhesive layer 3b of the protective layer 3 was fabricated as described below. First, as polyols, PREMINOL S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000), a polyol having three OH groups, SANNIX GP-3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000), and SANNIX GP-1000 (manufactured by Sanyo Chemical Co., Ltd., Mn=1000), a polyol having three OH groups, were used. Additionally, as a polyfunctional isocyanate compound, Coronate HX (manufactured by Nippon Polyurethane Kogyo Co., Ltd.), a polyfunctional alicyclic isocyanate compound, was used. Furthermore, as a catalyst, the trade name "NACEM Iron(III)" manufactured by Nippon Chemical Industry Co., Ltd. was used. Finally, as an anti-deterioration agent, Irganox 1010 (manufactured by BASF) was used. Additionally, isopropyl tetradecanoate (manufactured by Kao Corporation, trade name "EXCEPARL IPM", Mn=270) or hexadecyl 2-ethylhexanoate (manufactured by Nisshin OilliO Group Co., Ltd., trade name "SALACOS 816T", Mn=368) were used as fatty acid esters. Then, 1-ethyl-3-methylimidazole was added to these. A urethane adhesive composition was prepared by mixing and stirring bis(fluoromethanesulfonyl)imide (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., trade name "AS110"), a two-terminated polyether-modified silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KF-6004"), and ethyl acetate as a diluent. The prepared urethane adhesive composition was then applied to the substrate layer 3a using an impregnation roller to achieve a dried thickness of 10 μm. The mixture was then cured and dried at a drying temperature of 130°C for 30 seconds to form the adhesive layer 3b.

[0233] The protective layer 3 (AW700EC) comprises a substrate layer 3a and an adhesive layer 3b manufactured as described above. Then, the protective layer 3, the brittle material layer 1 of the laminate of the protective layer 3 and the optical functional layer 2 (the same as in Example 1) are bonded together via the adhesive layer 3b of the protective layer 3, thereby producing the composite material 10.

[0234] (2) When forming the second processing groove 31, the offset method is used.

[0235] (3) Figure 8 As shown, when forming the second processing tank 31, the output of the laser L2 oscillating from the second laser source 30 is set to 4.3W, and the resin is removed at the irradiation position in such a way that a portion of the resin (adhesive layer 3b) forming the protective layer 3 remains as residue (thickness: 7.5μm).

[0236] The end face of the brittle material layer 1 of the composite material 10 (composite material sheet) after being cut using the cutting method of Example 3 was visually observed, and the results are as follows: Figure 8 As shown, the brittle material layer 1 can be cut off without problems and without cracks.

[0237] <Example 4>

[0238] like Figure 8 As shown, when forming the second processing groove 31, the output of the laser L2 oscillating from the second laser source 30 was set to 4.9W, and the resin was removed at the irradiation position in such a way that a portion of the resin (adhesive layer 3b) forming the protective layer 3 remained as a residue with a thickness of 2.1μm. Apart from this, the composite material 10 was cut off under the same conditions as in Example 3.

[0239] The end face of the brittle material layer 1 of the composite material 10 (composite material sheet) after being cut using the cutting method of Example 4 was visually observed, and the results are as follows: Figure 8 As shown, the brittle material layer 1 can be cut off without problems and without cracks.

[0240] <Example 5>

[0241] like Figure 8 As shown, when forming the second processing groove 31, the output of the laser L2 oscillating from the second laser source 30 was set to 5.1W, and the resin was removed at the irradiation position in such a way that a portion of the resin forming the protective layer 3 was not left as residue (thickness: 0μm). Apart from this, the composite material 10 was cut off under the same conditions as in Example 3.

[0242] The end face of the brittle material layer 1 of the composite material 10 (composite material sheet) after being cut using the cutting method of Example 5 was visually observed, and the results are as follows: Figure 8 As shown, the brittle material layer 1 can be cut off without problems and without cracks.

[0243] <Comparative Example 2>

[0244] When forming the second processing groove 31, the protective layer 3 was irradiated only once with laser L2 oscillated by the second laser source 30 on the cut-off predetermined lines (set as multiple cut-off predetermined lines in a grid pattern) DL of the composite material 10 (without using the offset method). Except for this, the cut-off of the composite material 10 was attempted under the same conditions as in Example 5. Figure 8 As shown, the width of the second processing groove 31 formed in Comparative Example 2 is 30 μm, which is smaller than the spot diameter D (100 μm) at the irradiation position of the brittle material layer 1 by the laser L3 oscillating from the ultrashort pulse laser source 40 during the processing mark formation process.

[0245] like Figure 8 As shown, in the cutting method of Comparative Example 2, no processing mark 11 was formed through the brittle material layer 1, and the composite material 10 was not cut off.

Claims

1. A method for cutting a composite material, comprising cutting a composite material having a resin-based optical functional layer laminated on one side of a brittle material layer and a resin-based protective layer laminated on the other side of the brittle material layer. The protective layer comprises a substrate layer and an adhesive layer disposed on the side of the brittle material layer. The brittle material layer comprises glass. The method includes: The machining groove forming process, and the machining mark forming process following the machining groove forming process. In the process of forming the processing groove, the optical functional layer is irradiated with a laser emitted from a first laser source along a predetermined cut-off line of the composite material to remove the resin forming the optical functional layer, thereby forming a first processing groove along the predetermined cut-off line. Then, the protective layer is irradiated with a laser emitted from a second laser source along the predetermined cut-off line to remove the resin forming the protective layer in such a way that a portion of the adhesive layer remains in its thickness direction, thereby forming a second processing groove along the predetermined cut-off line. In the machining mark formation process, the brittle material layer is irradiated with a laser emitted from an ultrashort pulse laser source along the predetermined cut-off line from the second machining groove side, thereby removing the brittle material layer and forming a machining mark along the predetermined cut-off line. In the process of forming the processing groove, the resin used to form the protective layer is removed such that the width of the second processing groove is greater than or equal to the diameter of the light spot at the irradiation position described below. The irradiation position is the location where the brittle material layer is irradiated by the laser emitted from the ultrashort pulse laser source during the process of forming the processing mark. In the process of forming the processing tank, the protective layer is irradiated by a laser emitted from the second laser source at staggered positions along the predetermined cut-off line. Then, the resin present between the irradiation positions that forms the protective layer is peeled off, thereby forming the second processing tank. In the process of forming the machining marks, a laser oscillating from the ultrashort pulse laser source is irradiated from the second machining groove side, which is a portion of the adhesive layer remaining in the thickness direction, along the predetermined cut-off line to the brittle material layer.

2. A method for cutting a composite material, comprising cutting a composite material having a resin-based optical functional layer laminated on one side of a brittle material layer and a resin-based protective layer laminated on the other side of the brittle material layer. The protective layer comprises a substrate layer and an adhesive layer disposed on the side of the brittle material layer. The brittle material layer comprises glass. The method includes: The machining groove forming process, and the machining mark forming process following the machining groove forming process. In the process of forming the processing groove, the optical functional layer is irradiated with a laser emitted from a first laser source along a predetermined cut-off line of the composite material to remove the resin forming the optical functional layer, thereby forming a first processing groove along the predetermined cut-off line. Then, the protective layer is irradiated with a laser emitted from a second laser source along the predetermined cut-off line to remove the resin forming the protective layer in such a way that a portion of the adhesive layer remains in its thickness direction, thereby forming a second processing groove along the predetermined cut-off line. In the machining mark formation process, the brittle material layer is irradiated with a laser emitted from an ultrashort pulse laser source along the predetermined cut-off line from the second machining groove side, thereby removing the brittle material layer and forming a machining mark along the predetermined cut-off line. In the process of forming the processing groove, the resin used to form the protective layer is removed such that the width of the second processing groove is greater than or equal to the diameter of the light spot at the irradiation position described below. The irradiation position is the location where the brittle material layer is irradiated by the laser emitted from the ultrashort pulse laser source during the process of forming the processing mark. In the process of forming the processing groove, the laser emitted by the second laser source is used to irradiate the protective layer at staggered positions along the predetermined cut-off line in a direction orthogonal to the predetermined cut-off line, thereby forming the second processing groove. In the process of forming the machining marks, a laser oscillating from the ultrashort pulse laser source is irradiated from the second machining groove side, which is a portion of the adhesive layer remaining in the thickness direction, along the predetermined cut-off line to the brittle material layer.

3. The method for cutting the composite material according to claim 1 or 2, wherein, In the process of forming the processing tank, the resin that forms the protective layer is removed in such a way that the width of the second processing tank is 100 μm or more.

4. The method for cutting the composite material according to claim 1 or 2, wherein, The protective layer comprises a substrate layer and a urethane adhesive layer disposed on the side of the brittle material layer.

5. The method for cutting the composite material according to claim 1 or 2, wherein, The second laser source is a CO2 laser source.

6. The method for cutting the composite material according to claim 1 or 2, wherein, The optical functional layer includes a polarizing film.

Citation Information

Patent Citations

  • Manufacturing method of thin polarizing film

    JP2012073580A

  • Polarizing plate, fabrication method for polarizing plate, and image display device

    WO2013175767A1

  • Scribing method and scribing apparatus for composite substrate

    CN105693073A

  • Method of manufacturing glass interposer

    CN109256369A

  • Laser processing device

    JP2019025539A